Relationship between the novel and traditional anthropometric indices and subclinical atherosclerosis evaluated by carotid intima-media thickness (c-IMT) - Costo-Muriel, Clara; Calderón-García, Julián F.; Rico-Martín, Sergio; Galán-González, Javier; Escudero-Sánchez, Guillermo; Sánchez-Bacaicoa, Carmen; Rodríguez-Velasco, Francisco J.; Santano-Mogena, Esperanza; Fonseca, César; Muñoz-Torrero, Juan F. Sánchez (Frontiers in Nutrition, 2023)
Introduction Over the last few years, novel anthropometric indices have been developed as an alternative to body mass index (BMI) and other traditional anthropometric measurements to enhance the estimate of fat proportion and its relationship to a future cardiovascular event. The purpose of this study was to investigate the association of carotid intima-media thickness (c-IMT) estimated by Doppler ultrasound with current anthropometric indices (traditional and novel). Methods A cross-sectional study was conducted on a total of 789 Spanish patients. Traditional (BMI, WHR, and WHtR) and new (WWI, AVI, ABSI, BRI, BAI, CUN-BAE, and CI) anthropometric indices were determined, and carotid Doppler ultrasound was performed to evaluate c-IMT (≥0.90 mm). Results Most of the anthropometric indices analyzed were significantly higher among patients with pathological c-IMT, except for BMI, BAI, and CUN-BAE. In multiple linear regression analysis, c-IMT was positively related to ABSI, AVI, BRI, CI, and WWI but not to CUN-BAE, BAI, or traditional anthropometric indices. Similarly, in univariate analysis, all indices were associated with a c-IMT of ≥0.90 mm (p < 0.05), except BMI, BAI, and CUN-BAE; however, only ABSI (adjusted OR: 1.61; 95% CI: 1.08–2.40; p = 0.017), CI (adjusted OR: 1.73; 95% CI: 1.15–2.60; p = 0.008), and WWI (adjusted OR: 1.74; 95% CI: 1.14–2.64; p = 0.009) were significantly associated in multivariate analysis. Finally, CI, ABSI, and WWI provided the largest AUC, and BMI and CUN-BAE showed the lowest AUC. Conclusion ABSI, CI, and WWI were positively associated with pathological c-IMT (≥0.90 mm), independent of other confounders.